Haptic Bilateral Control System with Visual Force Compliance Controller - Jamaluddin, Muhammad Herman; Shimono, Tomoyuki; Motoi, Naoki (IEEE, 2013)
This paper presents a new haptic bilateral control method with vision-based guidance. The vision-based guidance is realized by the visual force compliance controller which can translate the visual information to assistive force. Integration of an imaging modality effectively further consolidates the servoing procedures. Such information needs to be efficiently rendered to the operator at master system. Particularly, the proposed approach provides real-time visualization and force feedback based guidance for the navigation task. The details concerning the method of implementation of this theory will be explained. Finally, the experimental evaluation of the functionality of this visual compliance controller based on force control is described and discussed.